Breast imaging : 12th International Workshop, IWDM 2014, Gifu City, Japan, June 29 - July 2, 2014. Proceedings - Hara, Takeshi; Muramatsu, Chisako; Fujita, Hiroshi (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 12th International Workshop on Breast Imaging, IWDM 2014, held in Gifu City, Japan, in June/July 2014. The 24 revised full papers and 73 revised poster papers presented together with 6 invited talks were carefully reviewed and selected from 122 submissions. The papers are organized in topical sections on screening outcomes, ultrasound, breast density, imaging physics, CAD, tomosynthesis and ICT and image processing.